Status of surfactants as penetration enhancers in transdermal drug delivery - Iti Som; Kashish Bhatia; Mohd. Yasir (Wolters Kluwer Medknow Publications, 2012)
Surfactants are found in many existing therapeutic, cosmetic, and agro-chemical preparations. In recent years, surfactants have been employed to enhance the permeation rates of several drugs via transdermal route. The application of transdermal route to a wider range of drugs is limited due to significant barrier to penetration across the skin which is associated with the outermost stratum corneum layer. Surfactants have effects on the permeability characteristics of several biological membranes including skin. They have the potential to solubilize lipids within the stratum corneum. The penetration of the surfactant molecule into the lipid lamellae of the stratum corneum is strongly dependent on the partitioning behavior and solubility of surfactant. Surfactants ranging from hydrophobic agents such as oleic acid to hydrophilic sodium lauryl sulfate have been tested as permeation enhancer to improve drug delivery. This article reviews the status of surfactants as permeation enhancer in transdermal drug delivery of various drugs.